Post‐Subduction Tectonics of Sabah, Northern Borneo, Inferred From Surface Wave Tomography. Issue 3 (4th February 2022) - Greenfield, Tim; Gilligan, Amy; Pilia, Simone; Cornwell, David G.; Tongkul, Felix; Widiyantoro, Sri; Rawlinson, Nicholas
Abstract: We use two‐plane‐wave tomography with a dense network of seismic stations across Sabah, northern Borneo, to image the shear wave velocity structure of the crust and upper mantle. Our model is used to estimate crustal thickness and the depth of the lithosphere‐asthenosphere boundary (LAB) beneath the region. Calculated crustal thickness ranges between 25 and 55 km and suggests extension in a NW‐SE direction, presumably due to back‐arc processes associated with subduction of the Celebes Sea. We estimate the β‐factor to be 1.3–2, well below the initiation of seafloor spreading. The LAB is, on average, at a depth of 100 km, which is inconsistent with models that ascribe Neogene uplift to wholescale removal of the mantle lithosphere. Instead, beneath a region of Plio‐Pleistocene volcanism in the southeast, we image a region 50–100 km across where the lithosphere has thinned to <50 km, supporting recent suggestions of lower lithospheric removal through a Rayleigh‐Taylor instability. Plain Language Summary: Understanding the tectonic processes, which have occurred after subduction has ended, is difficult because: (a) few well‐preserved, recent examples exist on the Earth, and (b) relatively few geophysical images have been made. This study calculates the shear wave velocity (Vsv) of the Earth beneath Sabah, in northern Borneo, using teleseismically detected earthquakes. We use these images of the Vsv to infer that extension dominates the geological history. In addition, we image a region where the lithosphere has dropped off. This correlates with a region of recent volcanism; presumably because of the upwelling hot rock induces melting of the mantle. Key Points: Shear wave model of Sabah, northern Borneo generated using the two‐plane‐wave method Crustal thickness and depth to the lithosphere‐asthenosphere boundary indicates back‐arc spreading behind the Celebes Sea slab In the south‐east corner, the lithosphere has been removed below a region of recent volcanism, possibly due a Raleigh‐Taylor instability